The Evaluation of Methodological Aspects of the Trade Enterprises Financial Stability Analysis - Savchenko, Illia; Nagorna, Iryna (Buhalterinės apskaitos teorija ir praktika, 2018)
[full article and abstract in English]Modern world trade trends put forward additional requirements for the trade enterprises to ensure efficient functioning and achieve a high level of competition. Considering this, it becomes actual to form and implement substantiated organizational and economic mechanism of financial stability analysis. The aim of the article is to substantiate the methodical aspects of the trade enterprises financial stability analysis in order to ensure the improvement of the economic assessment mechanism of its level. Research methods: generalization, analysis and synthesis. Key findings: the existing trends in the usage of the trade enterprises analytical apparatus are indicated the need for modernization of many methodical aspects of financial stability analysis. The author justified that it is advisable to adapt and implement in practice the structures of performance indicators in specific activity areas and structural divisions, to determine their impact significance on the integral indicator of the trade enterprise effectiveness.Prerequisites for improvement of the trade enterprises financial stability analysis system are revealed. Based on the scientific approaches evaluation the author developed methodological provisions of the complex analysis of the trade enterprises financial stability and highlighted the conceptual directions of the development and adaptation of existing methods to the real economy conditions. The main problems of ensuring the trade enterprises financial stability are revealed and ways of their solution are suggested. The theoretical provisions and methodological approaches discussed in the article can be used as the specific recommendations on the assessment of the trade enterprises financial stability and to develop an integrated model of such assessment. The scientific and methodological recommendations of the trade enterprises financial stability assessment that will contribute to the economic mechanism improvement for provision are proposed.
Keywords: financial stability, management, analysis, evaluation, trade enterprise